A Qur’anic account of biodiversity - Solihu, Abdul Kabir Hussain (2014)
Species diversity has been the hallmark of biosphere and invaluable resource for human being as well as for the natural environment. In order to appreciate and conserve these diverse species, different values have been proffered from different frames of references . This study examines biological diversity from the Qur’anic perspective in an attempt to explicate the kinds of value conferred by the Qur’an on non-human species among the animals and plants. Collating ayat (verses) of the Qur’an related to nonhuman species and analyzing key conceptual terms the Qur’an employs in reference to their diversity, the study found that nonhuman species are presented in the Qur’an as signs of Allah (s.w.t) and as communities (umam) of worshipers worthy of existence and conservation.